USAHA TANI TEMBAKAU UNTUK PENINGKATAN KESEJAHTERAAN KELUARGA ISLAMI PETANI TEMBAKAU DI DESA RANDUMERAK KECAMATAN PAITON KABUPATEN PROBOLINGGO - Aminah, Faiqotul; Ridho, Zainur (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2024)
Agriculture is crucial to Indonesia's economy, serving as a cornerstone for food security and sovereignty. Despite this, agricultural livelihoods have not significantly improved living standards in Indonesia's fertile lands. As one of the six major commodities, tobacco holds a strategic position in Indonesia's industry and exports, particularly to European countries. This research focuses on Probolinggo, a East Java regency known for producing high-quality tobacco. Despite the higher prices of tobacco in this region, the economic conditions of tobacco farmers are not always prosperous. Tobacco farming in Probolinggo has faced losses in recent years. The village of Randumerak, with a majority of its population engaged in tobacco farming, is the research subject to explore the household welfare levels of tobacco farmers. Various issues, such as the religious prohibition on smoking, the Tobacco Bill, and product price fluctuations prompt the study. Tobacco farmers in Randumerak face uncertainty and anxiety, especially during the tobacco planting season. This research aims to measure the household welfare levels of tobacco farmers, focusing on income and social conditions. By understanding these conditions, it is hoped that solutions or strategies can be identified to enhance the welfare of tobacco farmers amidst economic dynamics and regulatory changes related to tobacco.